THE IMPACT OF CAREER DEVELOPMENT AND WORKLOAD TOWARD EMPLOYEE JOB SATISFACTION AT PT ASKRINDO JAKARTA - Parimita, Widya; Pambudi, Wisnu Satrio; Aminah, Hania (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2017)
The purpose of this study are 1) determining the description of the workload, career development and job satisfaction in PT Askrindo, 2) testing empirically the effect of career development on job satisfaction at PT Askrindo, 3) testing empirically the effect of workload on job satisfaction at PT Askrindo, 4) empirically examining the influence of career development and workloads together on job satisfaction at PT Askrindo. Research conducted on 84 employees of PT Askrindo. The data collection technique using a survey method that is distributed questionnaires and processed by SPSS. This study used a descriptive analysis and explenatory. Results of regression showed that there is a significant positive effect between career development and job satisfaction, and there is a significant negative effect between workload and job satisfaction. Career development and work load together affect the job satisfaction of employees. Keywords: Job satisfaction, career development, workload.